PENGARUH MODEL TGT BERBANTU MEDIA GIMKIT TERHADAP KEAKTIFAN BELAJAR SISWA DI SEKOLAH DASAR - Maulida, Sonya Iklima; Nurasiah, Iis; Amalia, Arsyi Rizqia (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the effect of the Team Games Tournament (TGT) model assisted by Gimkit media on students’ learning engagement. The research employed an experimental method involving all third-grade students at SDN Karang Tengah, with a total population of 50 students—25 from class III A and 25 from class III B. Data collection was conducted using student learning activity observation sheets, while data analysis techniques included normality tests, homogeneity tests, and hypothesis testing. The results showed that both classes experienced improvement, with the average pre-test score in the control class being 51.5 and in the experimental class 49.9. The average post-test score in the control class was 58.9, while the experimental class reached 73.83. Although both groups showed improvement in student learning engagement, the experimental class demonstrated a higher level of engagement achievement compared to the control class. This was confirmed through the independent samples test, which yielded a Sig. (2-tailed) value of <0.001, which is less than the significance level of 0.05. This indicates that the use of the TGT model assisted by Gimkit media has a significant effect on increasing students’ learning engagement.